Nepal earthquake 2015 – an overview - Roy, Bedanta; Sathian, Brijesh; Banerjee, Indrajit (Journal of Biomedical Sciences, 2015)
Not available. DOI: http://dx.doi.org/10.3126/jbs.v2i1.13030 Journal of Biomedical Sciences 2015;2(1): 1-2